Laser induced fragmentation: from dissociation of neutrals to three-body breakup - Feizollah, Peyman (Kansas State University, 2018)
Ultrafast lasers allow us to study molecular dynamics on their natural timescale. The electronic dynamics can be studied using attosecond pulses, while the vibrational and rotational dynamics can be probed using tens of femtosecond and picosecond laser pulses, respectively. This capability has led to a broad understanding of the electronic dynamics in atoms and molecules as well as vibrational and rotational dynamics of molecules, which is one of the important goals in basic science. Moreover, it is possible to control quantum mechanical processes using ultrafast intense lasers. In this thesis, we focus on a couple of experiments. The first involves quantum control of the formation of neutral molecular fragments while the second focuses on three-body fragmentation of molecules employing the native-frames analysis method, which was recently introduced by our group [J. Rajput et al., Phys. Rev. Lett. 120, 103001 (2018)]. Experimental studies focused on the formation of excited neutral D fragments from D2 molecules are presented. We show that by manipulating the chirp of the intense laser pulses, i.e. the “time order” of the frequency components within the pulse, the formation of these fragments is controlled. To achieve this control we implement a single-prism compressor to manipulate the chirp of the laser pulses. Three-body fragmentation of CO₂ resulting in C+ + O+ + O+ is also studied. We show that if the two bonds break in a two-step process, i.e. a sequential breakup, the pathways from which the two identical O+ fragments originate can be separated using the native-frames analysis method. In contrast, the two O+ fragments cannot be distinguished if the two C-O bonds break simultaneously.
Keywords: Strong field physics; Quantum control; Imaging molecular fragmentation